2019
DOI: 10.1130/ges02074.1
|View full text |Cite
|
Sign up to set email alerts
|

Orogenic link ∼41°N–46°N: Collisional mountain building and basin closure in the Cordillera of western North America

Abstract: Polyphase structural mapping and mineral age dating across the Salmon River suture zone in west-central Idaho (Riggins region; ∼45°30′N, ∼117°W–116°W) support a late Mesozoic history of penetrative deformation, dynamothermal metamorphism, and intermittent magmatism in response to right-oblique oceanic-continental plate convergence (Farallon–North America). High-strain linear-planar tectonite fabrics are recorded along an unbroken ∼48 km west-to-east transect extending from the Snake River (Wallowa intra-oceani… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(6 citation statements)
references
References 263 publications
(527 reference statements)
0
6
0
Order By: Relevance
“…This magmatism is thought to reflect crustal anatexis in response to crustal thickening coeval with the ca. 75-100 Ma Sevier orogeny, e.g., [48][49][50][51], perhaps coupled with the input of mantle-derived mafic magma [52].…”
Section: Discussionmentioning
confidence: 99%
“…This magmatism is thought to reflect crustal anatexis in response to crustal thickening coeval with the ca. 75-100 Ma Sevier orogeny, e.g., [48][49][50][51], perhaps coupled with the input of mantle-derived mafic magma [52].…”
Section: Discussionmentioning
confidence: 99%
“…Some workers have suggested that terranes with island arc affinities, presently located in British Columbia, may have been translated northward along the western Idaho shear zone during middle to Late Cretaceous time (e.g., Giorgis et al, 2008;Wyld et al, 2006). One tectonic reconstruction places the Blue Mountains province very near to its modern day position in northeastern Oregon around ∼112 Ma (Gray et al, 2019). In contrast, other workers have interpreted that the Blue Mountains province may have been as far south as western Nevada around ∼110 Ma, allowing for the possibility that other outboard terranes may have occupied the Oregon-Idaho region during ROSENBLUME ET AL.…”
Section: Tectonic Setting and Regional Structurementioning
confidence: 99%
“…Given that the suture zone plutons represent only the westernmost edge of the present-day extent of the Idaho batholith (Gaschnig et al, 2010), the majority of the batholith is excluded as a potential source. The Blue Mountains province is currently situated to the west of the study area; it is an early Mesozoic collisional island arc and forearc assemblage with a complex accretionary and translational history (e.g., Dorsey & LaMaskin, 2007;Gaschnig et al, 2017;Gray et al, 2019;LaMaskin et al, 2011;Schwartz et al, 2010). Mesozoic plutons of the Blue Mountains province represent a potential sediment source for the 160 Ma detrital zircon grains in the study area.…”
Section: Potential Sediment Sourcesmentioning
confidence: 99%
See 1 more Smart Citation
“…To make it even more difficult to establish relationships between surface geology and deep structure, the SRP is largely covered in volcanics associated with the hotspot migration (e.g., Camp et al., 2015; Ellis et al., 2013). Despite these difficulties, multiple stages of deformation, exhumation of lower crustal material and zones of extensive shear have been reported along the edges of the SRP (e.g., Gray et al., 2020; Konstantinou et al., 2012; Tikoff et al., 2001). Most interestingly, Konstantinou and Miller (2015) postulate the existence of a long‐lived major lithospheric boundary below the SRP similar to the Lewis and Clark Shear zone further north taking up deformation associated with low angle subduction of the Farallon Slab.…”
Section: Density‐resistivity Relationshipsmentioning
confidence: 99%